Nadwyżka operacyjna jako narzędzie w procesie podejmowania decyzji finansowych w jednostkach samorządu terytorialnego - Filipiak, Beata (Operational Surrplus as an Instrument in Financial Decision Process in Local Self-Governments Units, 2007)
In the article are presented methods of preparation of operational surplus. There are described meaning of operational surplus as a source of information in local self-governments units. In the end of the article the author postulates changes in low and in budget procedure.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 146-153